Helicopter EMS Transport Outcomes Literature: Annotated Review of Articles Published 2007–2011 - Brandon S. Brown; Korby A. Pogue; Emily Williams; Jesse Hatfield; Matthew Thomas; Annette Arthur; Stephen H. Thomas (Emergency Medicine International)
Helicopter EMS (HEMS) and its possible association with outcomes improvement continues to be a subject of discussion. As is the case with other scientific discourse, debate over HEMS usefulness should be framed around an evidence-based assessment of the relevant literature. In an effort to facilitate the academic pursuit of assessment of HEMS utility, in late 2000 the National Association of EMS Physicians' (NAEMSP) Air Medical Task Force prepared annotated bibliographies of the HEMS-related outcomes literature. As a result of that work, two review articles, one covering HEMS use in nontrauma and the other in trauma, published in 2002 in Prehospital Emergency Care surveyed HEMS outcomes-related literature published between 1980 and mid-2000. The project was extended with two subsequent reviews covering the literature through 2006. This review continues the series, outlining outcomes-associated HEMS literature for the three-year period 2007 through the first half of 2011.